Tailoring crystallization phases in metallic glass nanorods via nucleus starvation. Issue 1 (December 2017) - Sohn, Sungwoo; Xie, Yujun; Jung, Yeonwoong; Schroers, Jan; Cha, Judy
Abstract Many physical phenomena deviate from their established frameworks when the system approaches relevant length scales governing the phenomena. In crystallization, the relevant length scales are the nucleation length set by the nucleus size and density, and the growth length set by diffusion fields. Here we observe unexpected crystallization phenomena at the nanoscale, using metallic glass (MG) nanorods and in situ transmission electron microscopy. The asymmetry between critical heating and cooling rates disappears for small MG nanorods. Strikingly, an apparent single crystalline phase with its composition similar to the glass composition is observed for very small rods, in contrast to bulk samples. We attribute this to the lack of nuclei in small MG nanorods that approach the nucleation length, thus coined the term, nucleus starvation. By controlling the MG nanorod diameter and crystallization kinetics, we can tune the number of nuclei in a nanorod, thereby tailoring the resulting crystallization phases. Crystallising a bulk metallic glass usually results in separate phases. Here, the authors use metallic glass nanorods to show that as the sample size approaches the nucleation scale lengths, the crystallization behavior is dictated by the lack of nuclei and nanorods crystallise into a single phase.